3
$\begingroup$

I was working on some math problems on Khan Academy and wondered why does the negative '-' sign go away when the following radical expression is simplified? In particular how does one obtain the equality $$\frac{-4}{-6} \pm \color{red}{-}\frac{2\sqrt{7}}{6} = \frac{2}{3} \mp \frac{7}{\sqrt{3}}$$ enter image description here

$\endgroup$
  • $\begingroup$ it is not gone, but $(\pm) \cdot (-) = (\mp)$ $\endgroup$ – farruhota May 27 '17 at 14:07
3
$\begingroup$

We have $$a\pm -b = \begin{cases}a+ -b = a-b\\ a--b = a+b\end{cases} = a\mp b;$$can you see how this applies to your situation?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.